Should I Buy It Again?: Analisis Faktor Determinan terhadap Purchase Decision dan Repurchase Intention Brand di Tiktok Shop via Live Shopping - Vinco Valerio; Usep Suhud; Meta Bara Berutu (Indo Publishing, 2026)
This study aims to analyze the factors influencing purchase decision and repurchase intention in TikTok live shopping. The variables examined include social influence, information quality, and interactivity, using a quantitative research approach. Data were collected through an online survey distributed to respondents who had previously made purchases via TikTok’s live shopping feature. SEM was employed to examine the relationships among variables. The results indicate that information quality and interactivity have a significant positive effect on purchase decision, while interactivity also contributes to repurchase intention. Conversely, social influence shows a negative effect on purchase decision and does not significantly affect repurchase intention. These findings suggest that clear product information and active engagement by live shopping hosts play a crucial role in driving audience conversion. This study contributes theoretically by reinforcing Social Presence Theory and provides practical insights for businesses in developing effective live shopping strategies that emphasize trust, interaction quality, and customer satisfaction.